International Obligations on Atmosphere and Climate Protection in Media Discourse: Propaganda Models of Russian and US Media - Radina, Nadezhda; Bobkova, Sofya (Communication Today, 2021)
The aim of the study is to compare the strategies of the Russian and American media in justifying the need to comply with international obligations on atmosphere and climate protection in the context of solving national propaganda tasks and to describe their dominant propaganda models. The research methods comprise the technique of intent-analysis by Ushakova and Pavlova, as well as the technique of rhetorical deconstruction by Ibarra and Kitsuse. Empirical materials of the research include texts of the of Russian and American media (Izvestia, Rossiyskaya Gazeta, Gazeta.Ru, The New York Times, The Washington Post, USA Today: 104 articles in total; published from 1st January 2012 to 1st January 2017). It was found that the propaganda models of the Russian and American media correspond to the description of propaganda within the state by Ellul under the two-party system of the state: the ruling party conducts propaganda for itself, the opposition party conducts propaganda against the ruling party. The propaganda model of the American media in this area of information competition between the two states can be characterised as the “propaganda model of the leader”, and the propaganda model of the Russian media may be called the “opposition propaganda model”.